2016
DOI: 10.1021/acs.jpcc.6b09553
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Solid-State Ion Exchange of Cu+ into Zeolites

Abstract: Density functional theory calculations are used to investigate solid-state ion exchange of copper into zeolites. In particular, the energetic conditions for functionalization of chabazite (CHA) with copper ions from Cu2O­(111) via formation of Cu­(NH3)2 + are explored. It is found that the diamine complexes form easily on Cu2O­(111) and diffuse with low barriers over the surface and in the CHA framework. The charge neutrality of the systems is maintained via counterdiffusion of H+ in the form of NH4 + from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
4
42
0
Order By: Relevance
“…For non Cu-exchanged CHA, it has been shown that protons balancing Si-OIJ-)-Al preferably occupy a four-membered ring adjacent to the Al positions. 23 Here, we only consider such positions for H + .…”
Section: Formation Of Cuijnh 3 ) 2 + Pairsmentioning
confidence: 99%
See 2 more Smart Citations
“…For non Cu-exchanged CHA, it has been shown that protons balancing Si-OIJ-)-Al preferably occupy a four-membered ring adjacent to the Al positions. 23 Here, we only consider such positions for H + .…”
Section: Formation Of Cuijnh 3 ) 2 + Pairsmentioning
confidence: 99%
“…[15][16][17]21,22 This complex is mobile and weakly bonded to the zeolite framework. 23 At higher temperatures, NH 3 desorbs and Cu is coordinated directly to the zeolite framework with lost mobility. 16,17,22 Density functional theory (DFT) calculations have shown that dissociation of O 2 on a pair of Cu-ions is considerably faster than on single Cu ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental as well as computational studies have shown that Cu + is preferably solvated by two NH 3 ligands forming a linear [Cu(I)(NH 3 ) 2 ] + complex under low-temperature NH 3 -SCR conditions [18][19][20][21][22][23][24]. The [Cu(I)(NH 3 ) 2 ] + complex is mobile with low barriers for inter-cage diffusion and suggested to be important also for the solid-state ion-exchange reaction [25]. In addition to Cu + species, Cu-CHA also contain solvated Cu 2+ species in the form of [Cu(II)( [15,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that copper becomes mobile at low temperature, in the presence of NH 3 , owing to the formation of [Cu(NH 3 ) 2 ] + complexes. By including NO during the exposure to NH 3 , the migration rate of Cu into the porous structure of the zeolite is enhanced and it was suggested that NO assists the reduction of Cu 2+ in CuO to Cu + , which with ammonia forms the mobile [Cu(NH 3 ) 2 ] + complexes [16,17]. The so-called [NO+NH 3 ]-SSIE method is simple as it only involves two operation steps (mixing the CuO and zeolite powders, and flushing ammonia and NO over the mixture), both in the absence of aqueous media, and can be performed at considerably lower temperatures compared to conventional solid-state ion-exchange in air.…”
Section: Introductionmentioning
confidence: 99%